Generalized weakly a-contractive mappings and applications to ordinary differential equations - Işık, Hüseyin; Türkoğlu, Duran (University of Miskolc, 2016)
In this paper, we introduce the notion of generalized weakly a-contractive mappings and give some common fixed point results for this type of contraction. The presented theorems extend, generalize and improve many existing results in the literature. Two examples as well as an application to ordinary differential equations are also given in order to illustrate the effectiveness of the obtained results. © 2016 Miskolc University Press.
Keywords: Common fixed point; Generalized weakly a-contraction; Point of coincidence; Two point boundary value problem; Weakly compatible mappings